Allogeneic Transplantation: Peripheral Blood versus Bone Marrow - Bensinger, William I. (2012)
PURPOSE OF REVIEW: Peripheral Blood Stem Cells (PBSC) have been widely adopted as a source of stem cells for allogeneic transplantation although controversy remains regarding their role compared to the use of bone marrow (BM). RECENT FINDINGS: Ten year follow-up has been reported from several large randomized trials and a recently completed trial using unrelated donor stem cells have been reported. In addition, two meta-analyses have been reported from the findings of a number of randomized studies. Several studies indicate that PBSC confer survival advantages over BM with matched sibling donors for most disease categories except where the risks of disease recurrence within the first year are low, but with the extra risk of more chronic GVHD. Using PBSC from unrelated donors does not appear to be more beneficial than BM, but with early follow-up. New strategies for rapid mobilization of PBSC from normal donors using plerixafor have been reported. Early studies suggest that filgrastim stimulated BM may confer some of the advantages of PBSC without the risks of chronic GVHD. SUMMARY: PBSC are a preferred source of stem cells for many types of allogeneic transplant where matched related donors are available. Whether the same benefits accrue from unrelated donors will require further follow-up.